Masculinity in The Characters of Sally and Jo in The Film Misbehaviour - Syafrilla Kurniasi; Pita Merdeka; Maria Ulfa; Nina Farlina (Universitas Teknokrat Indonesia, 2022)
This article discusses the masculinity of the female characters, Sally Alexander and Jo Robinson, in the film Misbehaviour. Thus, this article aims to analyze the masculinity within women by focusing on the characters’ analysis of Sally Alexander and Jo Robinson. The article uses a descriptive qualitative method and takes the data from the film in the form of captured scenes and dialogues. The article uses the theory of character and characterization from Boggs and Petrie to find out the masculine characteristics of Sally and Jo and also the concept of masculinity by Peter Lehman to support the argument. Based on the findings, this research shows that Sally and Jo live in a patriarchal society and establish characteristics that can be considered masculine. Sally’s ambitious, forward-thinking, well-organized, activeness, and negligence, and Jo’s daring, indiscipline, nonchalance, aggressiveness, and independence, establish their masculinity in the form of courage, heroism, and leadership, appearance, and other behaviors, for instance, smoking. Moreover, their characteristics have both merits and shortcomings. Indeed, their experience, environment, and societal factors influence their masculine characteristics